Anti CD38 monoclonal antibodies for multiple myeloma treatment - Alessandro Gozzetti; Sara Ciofini; Martina Simoncelli; Adele Santoni; Paola Pacelli; Donatella Raspadori; Monica Bocchia (Taylor & Francis Group, 2022)
CD38 is a transmembrane glycoprotein with ectoenzymatic activity and is highly and uniformly expressed on multiple myeloma (MM) cells. CD38 is expressed also at relatively low levels on normal lymphoid and myeloid cells, and in some tissues of non-hematopoietic origin. The specificity of this target has increased interest in new drugs and triggered the development of the CD38 monoclonal antibodies Daratumumab (fully human) and Isatuximab (chimeric). CD38 antibodies have pleiotropic mechanisms of action including Fc-dependent immune effector mechanisms, direct apoptotic activity, and immunomodulatory effects by the elimination of CD38+ immune-suppressor cells. Monoclonal antibody-based therapy has revolutionized MM therapy in the latest years increasing depth of response. This product review will focus on anti-CD38 monoclonal antibodies Daratumumab and Isatuximab efficacy, safety, pharmacokinetic and pharmacodynamic data from clinical trials.